Occupational dental wear among El-Kubasis cement factory workers - An observational study - Mohammed I Abdulla; Athraa M Al-Waheb (College of Dentistry/ University of Baghdad, 2014)
Background: Loss of tooth structure may be due to tooth to tooth contact and presence of abrasive components in the work environment. The aim of study was planned to evaluate the occurrence of dental attrition among Cement factory workers. Material and Method: The Sample included all workers chronically exposed to cement dust in the EL-Kubaisa cement factory (95 workers). A comparative group of workers (97) were non-exposed to cement dust was selected. All workers were males in gender with age range (25-55) years. The assessment of tooth wear was based on the criteria of smith and knight, 1984. Results: The maximum tooth wear score for exposed workers was 84.2% while non exposed workers was 38.1%,with statistical differences between two groups was highly significant (P 0.05). Conclusion: Work environment was related to dental wear.